Gambaran Tingkat Kecemasan Mahasiswa Fakultas Kedokteran Universitas Mulawarman Sebelum Menghadapi OSCE: An Overview of Anxiety Levels of Medical Faculty Students Mulawarman University Before OSCE - Devi Permata Sari; Hary Nugroho; Abdillah Iskandar (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Anxiety is a very familiar term that describes a state of worry, anxiety, fear, and in peace with various physical grievances. Medical students experience a level of mental exhaustion that includes anxiety. Medical faculty students have a hectic schedule of lectures, tutorial activities, practicum, lab skills and the demands to study independently outside those hours so that the pressure on physical and mental conditions is relatively more severe than other education. In addition to learning activities, medical students also conduct Objective Structural Clinical Examination (OSCE) exams as an instrument testing clinical skill of medical students. The many thoughts about the material to be learned between theory, clinical skills in the OSCE exam, osce atmosphere, OSCE testers observing participants directly, unpreparedness following the OSCE, OSCE mechanism and the same time interval of each stase make osce known as a test that causes quite high anxiety. This research aims to find out the picture of anxiety levels of students of The Faculty of Medicine Universitas Mulawarman before facing the OSCE. This research is a descriptive observational study with cross-sectional design. Sampling using stratified random sampling techniques. This level of anxiety was measured using the English version of the Hamilton Anxiety Rating Scale (HARS) questionnaire which was translated into Indonesian with 14 items. The sample was obtained by 96 students. In this study, 27 students (28.12%) with mild anxiety levels, 29 students (30.21%) with mild to moderate anxiety levels, 40 students (41.67%) with moderate to severe anxiety levels.